Analysis Unit Cost In Mild Head Injury Patient With Activity Based Costing Method At The Hopital In Yogyakarta - Kurniawan, Sigit; Pribadi, Firman (Archives of Business Research, 2018)
Background: The system used by the government to payment of tariff claim to hospital is by using INA-CBG’s system (Indonesian Case Based Groups). The implementation of INA-CBG’s system by the government make hospitals need to analyze expenditure cost in patient treatment, and take effort to effectively reduce cost expended, one of those is by using clinical pathway. Panembahan Senopati Bantul hospital has never conducted a cost evaluation based on clinical pathway for mild head injury, only in the case of appendicitis has been evaluated based on clinical pathway and compared with INA-CBG tariff obtained positive difference, the costs incurred by Hospitals are lower compared to INA-CBG "s tariff claims. One of the cost calculations in the hospital, by using analysis of unit cost. Research Objective: To analyzed the unit cost in mild head injury patient with Activity Based Costing method in Panembahan Senopati Bantul hospital. Method: This research did in Panembahan Senopati Bantul hospital. This research was kind of quantitative descriptive research. The subject of this research is chief financial officer, Surgical Specialist, Head of Ward Melati, pharmacy officer, medic record officer and mild head injury patient. Data analysis method used was Activity-Based Costing (ABC). Result: Unit cost calculation on inpatients with head injury diagnosis by Activity Based Costing method at Panembahan Senopati Bantul hospital obtained total cost as much Rp.2,301,989.30. Unit cost with ABC method got difference between unit cost with real cost according to policy applied in RSUD Panembahan Senopati Bantul with difference of cost equal to Rp. 84.357,70. Unit cost with ABC method got difference between unit cost with INA CBG’s tariff which set by the government with difference of cost equal to Rp.146.810,70. Conclusion: Unit cost in mild head injury patients with ABC method in Panembahan Senopati Bantul hospital obtained lower cost than the real cost and INA CBG’s tariff. Keywords: Activity-Based Costing (ABC), Unit Cost, Mild head injury